Fixed Point Theorems of Wardowski Type Mappings in S_b-Metric Spaces: Muhammad Anwar, Dur-e-Shehwar Sagheer, Rashid Ali, Samina B atul - Team, Support (Thai Journal of Mathematics, 2022)
In this paper, we introduced the concept of (α,F)-contractive pair in the structure of S_b-metric spaces. And we generalized the Wardowski type mappings in this structure and proved the fixed point and common fixed point theorems for (α,F)-contractive pair with some suitable conditions. Furthermore, we give some examples for the guarantee of the main theorems.